PENGARUH KOMPOSISI GULA TERHADAP KETAHANAN SIMPAN DAN CITA RASA MANISAN TOMAT KERING - Nikmat Akmal; Sulistiawikarsih Sulistiawikarsih (JURNAL KELUARGA SEHAT SEJAHTERA, 2020)
ABSTRACTThe aims of this study were: (1) to determine whether there are differences in taste (color, aroma, texture and taste) of dried tomato candied with a sugar composition (40%, 50%, 60% and 70%); (2) to find the sugar composition that has the best shelf life with the best taste. Independent variable is sugar and dependent variable were shelf life and taste. The assessment was carried out by five panelists through the organoleptic test. Data were analyzed descriptively and different test with the Two-Independent-Samples Test statistic with the Mann-Whitney U-Wilcoxon Rank Sum W Test. The shelf life was analyzed from the second taste assessment plus the observation of the appearance of the fungus.           Keywords: Dried Tomato Candied, Composition of Sugar ABSTRAKPenelitian ini bertujuan: (1) mengetahui apakah ada perbedaan  cita rasa  (warna, aroma, tekstur dan rasa) manisan tomat kering dengan komposisi gula (40%, 50%, 60% dan 70%); (2) menemukan komposisi gula yang memiliki daya tahan simpan dengan cita rasa  terbaik.  Ubahan bebas adalah gula pasir, ubahan terikat (1) ketahanan simpan; (2) cita rasa.   Penilaian dilakukan lima panelis melalui uji organoleptik. Data dianalisis secara deskriptif dan uji beda dengan statistik Two-Independent-Samples Test dengan uji Mann-Whitney U-Wilcoxon Rank Sum W Test. Ketahanan simpan dianalisis dari cita rasa penilaian ke dua ditambah pengamatan penampakan jamur. Kata Kunci: Manisan Tomat Kering, Komposisi Gula